How sick is Austria? - A decision support framework for different evaluations of the burden of disease within the Austrian population based on different data sources. (2017) - Glock, Barbara; Endel, Florian; Endel, Gottfried; Sandholzer, Klaudia; Popper, Niki; Rinner, Christoph; Duftschmid, Georg; Filzmoser, Peter; Mert, Mehmet Can; Holl, Jürgen; Wagner-Pinter, Michael
No abstract available